Risk factors and glycation end products in patients with different forms of coronary heart disease and type 2 diabetes mellitus - E V Ivannikova; V Yu Kalashnikov; O M Smirnova; I V Kononenko; A B Kuznetsov; S A Terekhin (Терапевтический архив, 2015)
Aim. To determine the levels of growth factors and glycation end products in patients with different forms of coronary heart disease (CHD) and type 2 diabetes mellitus (T2DM). Subjects and methods. A total of 134 patients with CHD and T2DM, including 38 patients with non-ST-elevation acute coronary syndrome (ACS), were examined. The arterial and venous serum levels of basic fibroblast growth factor-β (FGF-β), transforming growth factor-β (TGF-β), placental growth factor (PlGF), advanced glycation end products (AGEs) and their receptors (RAGE) were estimated in all the patients. Results. A direct correlation was found between the degree of arterial stenosis and the level of growth factors and AGEs in the patients with T2DM; there was also a direct correlation of the examined factors with lipid metabolic parameters. There was a significant two-fold increase in FGF-β, PlGF, and RAGE levels in the patients with ACS. Conclusion. Hyperglycemia was found to negatively affect the progression of atherosclerotic changes in the vessel wall and on that of fibrotic processes.